Language and social cognition: expression of the social mind - Pishwa, Hanna (Trends in linguistics, 2009)
Introduction: linguistic structures as carriers of social-cognitive functions / Hanna Pishwa -- Section I: Social cognition and language: 1. The origin of the social approach in language and cognitive research exemplified by studies into the origin of language / Nathalie Gontier -- 2. Fused Bodies: Sense-making as a phenomenon of interacting, knowledgeable, social bodies / Anders R. Hougaard & Gitte R. Hougaard -- 3. Supracultural models, universalism and relativism: Chinese and American views of personhood / Jason D. Patent -- 4. On collective cognition / Farzad Sharifian -- 5. The development of Turkish and Finnish words related to privacy / Mai Kuha and M. Ali Bolgün -- Section II: Social cognition and discourse : 6. The creative construction of social orientation : Situated positioning with English as a lingua franca / Andreas Langlotz -- 7. Distributed cognition and play in the quest for the double helix / David Ritchie -- 8. Social Aspects of Verbal Irony Use / Roger J. Kreuz and Gina M. Caucci -- 9. Conversational pragmatics and social cognition / Thomas Holtgraves and Blake M. Anderson -- 10. Corporate self-presentation and self-centredness: a case for cognitive Critical Discourse Analysis / Veronika Koller -- 11. Constructing knowledge schemas in the workplace: A microanalysis / Susan Bridges and Brendan Bartlett -- Section III: Social cognitive functions of single structures: 12. Attribution Theories Wired Into Linguistic Categories / Klaus Fieder and Peter Freytag -- 13. Metaphor in mental representations of space, time and society: the cognitive linguistics approach / Paul Chilton -- 14. Emotion talk and emotional talk: cognitive and discursive perspectives / Monika Bednarek -- 15. From motion to emotion to interpersonal function: The case of fear predicates / Eliza Kitis -- 16. Tuned to hidden messages: Exploring recurrent word combinations in English / Rainer Schulze